Réponses

2014-03-05T00:45:55+01:00
A = x + 4x = 5x

B = 3y2 - 2y2 = 6y - 4y = 2y

C = 3a2 - 7a2 = 6a - 14a = (-8a)

D = -7x + 5 + 9a - 6 + x - 6a
D = -6x+ 3a -1

E = 10x2 - 5 + 2x - 9x2 + 3
E = 20x - 5 + 2x - 18x + 3
E = 4x - 2

F = 5a - 6y + 3a + 4y - 2a
F = 6a - 2y
2014-03-05T01:02:56+01:00

A=x+4x

A= x(1+4) = 5x

B=3y2-2y2

B = y (6 - 4) = 2 y

C=3a2-7a2

C =a (6 - 14) = -8a 

D=-7×+5+9a-6+x-6a

D=-7x+x+5-6+9a-6a

D= - 6x + 3a -1     

E=10x2-5+2x-9x2+3

E= 20 x -5 + 2x - 18x + 3

E= 4x + 2


F=5a-6y+3a+4y-2a

F=6a -2y